The ethical dimension of translation revision. An empirical study. - Alexander Künzli (JoSTrans: The Journal of Specialised Translation)
This paper investigates translation revision using think-aloud protocols. Ten professional translators were asked to think aloud while revising three draft translations. The focus of the analysis is on a specific aspect of the ethics of translation revision: the reviser’s (sense of) loyalty to the different parties involved in a prototypical freelance translation revision job mediated by a translation agency. The findings reveal a number of potential loyalty conflicts and ethical dilemmas. They also indicate the need to consider situational factors such as time constraints when evaluating the product and process of translation (revision).